2021
DOI: 10.1101/2021.08.02.21261509
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sensitive and multiplexed RNA detection with Cas13 droplets and kinetic barcoding

Abstract: SUMMARYRapid and sensitive quantification of RNA is critical for detecting infectious diseases and identifying disease biomarkers. Recent direct detection assays based on CRISPR-Cas13a1–4 avoid reverse transcription and DNA amplification required of gold-standard PCR assays5, but these assays have not yet achieved the sensitivity of PCR and are not easily multiplexed to detect multiple viruses or variants. Here we show that Cas13a acting on single target RNAs loaded into droplets exhibits stochastic nuclease a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…Our engineered CRISPR-Cas system is among one of the most sensitive CRISPR-based amplification-free technologies for the detection of nucleic acid developed to date in detecting the SARS-CoV-2 genome (LoD 0.6 copies per microliter in the reaction, within 30 min). It shows comparable sensitivity to the droplet-based Cas13a kinetic barcoding (below 1 copy per microliter), which contained a total of 26 crRNAs in one single assay 49 ; it is one order of magnitude more sensitive than that of the Cas13a-Csm6 tandem assay (31 copies per microliter), which required eight different crRNAs and a Csm6 protein with its chemically modified activator RNA 17 ; two orders of magnitude more sensitive than the Cas13a-mobile phone microscopy (200 copies per microliter), which utilized three different crRNAs 16 ; three orders of magnitude more sensitive than the Cas13-microchamber array 14 , and six orders of magnitude more sensitive than the CRISPR-electrochemical biosensor that depends on the WT Cas13a protein 18 . As opposed to the aforementioned amplification-free detection technologies that are exclusively based on extracted RNA materials, our RBD-LwaCas13a-electrochemistry platform showed great detection sensitivity and accuracy and does not need the additional RNA extraction steps, which holds great potential for ultrasensitive detection of various RNAs of clinical and environmental importance.…”
Section: Discussionmentioning
confidence: 97%
“…Our engineered CRISPR-Cas system is among one of the most sensitive CRISPR-based amplification-free technologies for the detection of nucleic acid developed to date in detecting the SARS-CoV-2 genome (LoD 0.6 copies per microliter in the reaction, within 30 min). It shows comparable sensitivity to the droplet-based Cas13a kinetic barcoding (below 1 copy per microliter), which contained a total of 26 crRNAs in one single assay 49 ; it is one order of magnitude more sensitive than that of the Cas13a-Csm6 tandem assay (31 copies per microliter), which required eight different crRNAs and a Csm6 protein with its chemically modified activator RNA 17 ; two orders of magnitude more sensitive than the Cas13a-mobile phone microscopy (200 copies per microliter), which utilized three different crRNAs 16 ; three orders of magnitude more sensitive than the Cas13-microchamber array 14 , and six orders of magnitude more sensitive than the CRISPR-electrochemical biosensor that depends on the WT Cas13a protein 18 . As opposed to the aforementioned amplification-free detection technologies that are exclusively based on extracted RNA materials, our RBD-LwaCas13a-electrochemistry platform showed great detection sensitivity and accuracy and does not need the additional RNA extraction steps, which holds great potential for ultrasensitive detection of various RNAs of clinical and environmental importance.…”
Section: Discussionmentioning
confidence: 97%
“…69 They showed that the LOD was improved 100-fold with the same CRISPR reaction time. In another study, Son et al 72 utilized 26 different crRNAs in a Cas13a assay and improved the LOD 5 times. It is clear that utilizing multiple crRNAs could decrease the FOM value and improve the system performance.…”
Section: ■ Fom Improvement Strategiesmentioning
confidence: 99%
“…It is noteworthy that multiple strategies could be implemented in one system to achieve lower FOM compared to individual strategies. For instance, Son et al 72 combined digitalization and multiple crRNA in a single system and reduced the FOM by more than 6 orders of magnitude compared to the nonamplified Sherlock system. 9 To guide the implementation of improvement strategies for different applications, we summarized the advantages and disadvantages of each strategy in Table 1.…”
Section: ■ Fom Improvement Strategiesmentioning
confidence: 99%
See 2 more Smart Citations